Perceived constraints and challenges in compliance and implementation of the OBE syllabus of West Visayas State University-Extension Campus at Himamaylan City - Casiano, Mary Lord L (University of the Philippines Visayas, 2017)
This study aimed to investigate the perceived challenges and constraints in the compliance and implementation of Outcome-Based Education syllabus by the teachers who are handling Social Science courses at West Visayas State University-Extension Campus at Himamaylan City. Data were obtained through the use of Triangulation Method in the forms of Survey Questionnaire, Focus Group Discussion and Document Analysis. Results showed that teachers' understanding from trainings and seminars workshops attended was not enough because it was only limited to the format to be used and not on the application inside the classroom. In terms of the submission of OBE syllabus, there was monitoring but lack of feedback with regards to the content. It is recommended therefore that teachers may attend trainings because training implies application. The school may as well organize a monitoring mechanism in the implementation of OBE syllabus inside the classroom. Lastly, close monitoring is highly recommended to properly address the problems of implementation of the OBE program.